A hybrid Delphi-AHP multi-criteria analysis of Moving Block and Virtual Coupling railway signalling. (August 2021) - Aoun, Joelle; Quaglietta, Egidio; Goverde, Rob M.P.; Scheidt, Martin; Blumenfeld, Marcelo; Jack, Anson; Redfern, Bill
Highlights: A hybrid Delphi-AHP to assess impacts of railway signalling innovations. A multi-criteria analysis framework with quantitative and qualitative criteria. Quantitative criteria are based on operational scenarios for five market segments. Virtual Coupling outperforms Moving Block when assuming similar safety levels. Abstract: The railway industry needs to investigate overall impacts of next generation signalling systems such as Moving Block (MB) and Virtual Coupling (VC) to identify development strategies to face the forecasted railway demand growth. To this aim an innovative multi-criteria analysis (MCA) framework is introduced to analyse and compare VC and MB in terms of relevant criteria including quantitative (e.g. costs, capacity, stability, energy) and qualitative ones (e.g. safety, regulatory approval). We use a hybrid Delphi-Analytic Hierarchic Process (AHP) technique to objectively select, combine and weight the different criteria to more reliable MCA outcomes. The analysis has been performed for different rail market segments including high-speed, mainline, regional, urban and freight corridors. The results show that there is a highly different technological maturity level between MB and VC given the larger number of vital issues not yet solved for VC. The MCA also indicates that VC could outperform MB for all market segments if it reaches a comparable maturity and safety level. The provided analysis can effectively support the railway industry in strategic investment planning of VC.